Ask a question



1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Andre W. | Friendly tutor for ALL math and physics coursesFriendly tutor for ALL math and physics ...
5.0 5.0 (3 lesson ratings) (3)
Check Marked as Best Answer
= 2∫√(x²+10x)dx
= 2∫√((x+5)²-25)dx
= 2∫√(u²-25)du , u=x+5
This is a standard integral, which you can look up in a table. You find
2∫√(u²-25)du = u √(u²-25) -  25 ln (u+√(u²-25)) +c, so that
∫√(4x²+40x)dx= (x+5) √((x+5)²-25) -  25 ln (x+5+√((x+5)²-25)) +c
= (x+5) √(x²+10x) -  25 ln (x+5+√(x²+10x)) +c
Let me know if you want to see how the formula for the standard integral can be derived.